2015
DOI: 10.18632/oncotarget.3631
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 and 5 expression decreases during human intervertebral disc degeneration: novel HIF-1-mediated regulation of aquaporins in NP cells

Abstract: Objectives of this study were to investigate whether AQP1 and AQP5 expression is altered during intervertebral disc degeneration and if hypoxia and HIF-1 regulate their expression in NP cells. AQP expression was measured in human tissues from different degenerative grades; regulation by hypoxia and HIF-1 was studied using promoter analysis and gain- and loss-of-function experiments. We show that both AQPs are expressed in the disc and that mRNA and protein levels decline with human disease severity. Bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 50 publications
(63 reference statements)
2
51
0
Order By: Relevance
“…After 24 hours of treatment with TNF-α, hydraulic permeability and cell radius of NP cells were altered for 1 week (Maidhof et al, 2014). These authors also noted a decrease in the expression of water channel Aquaporin 1, which has been recently shown to be associated with severity of degenerative disc disease (Maidhof et al, 2014; Johnson et al, 2015). Similarly, in a bovine disc organ culture model, short-term TNF-α treatment has been shown to result in long-term catabolic effects without negatively affecting cell viability (Purmessur et al, 2013).…”
Section: Tnf and Il-1 Affect Homeostatic Activities Of Ivd Cellsmentioning
confidence: 82%
“…After 24 hours of treatment with TNF-α, hydraulic permeability and cell radius of NP cells were altered for 1 week (Maidhof et al, 2014). These authors also noted a decrease in the expression of water channel Aquaporin 1, which has been recently shown to be associated with severity of degenerative disc disease (Maidhof et al, 2014; Johnson et al, 2015). Similarly, in a bovine disc organ culture model, short-term TNF-α treatment has been shown to result in long-term catabolic effects without negatively affecting cell viability (Purmessur et al, 2013).…”
Section: Tnf and Il-1 Affect Homeostatic Activities Of Ivd Cellsmentioning
confidence: 82%
“…Our results suggest Aqp3 and TRPV4 may be important osmoregulators in the IVD, and Aqp3 is a possible osmoregulatory channel regulating NC differentiation to sNPCs. Previous studies have shown Aqp3 expression decreases with IVD aging and degeneration . Thus, Aqp3 may be important for osmoregulation in the healthy, highly‐hydrated IVDs with vacuolated NCs, and its function and therefore expression may be less important in degenerated or aged IVDs.…”
Section: Discussionmentioning
confidence: 95%
“…Aqps are a family of osmosensitive transmembrane proteins ubiquitously expressed throughout the body, including the IVD, and can control intracellular water equilibrium and cell volume under hyperosmolar and hypoosmolar conditions by selectively shuttling water and certain solutes in and out of cells . Aqps1 and 3 expressions have been shown to decrease with IVD degeneration and aging . The loss of the juvenile NC phenotype was recently reported to involve a loss of N‐cadherin expression (N‐cad), suggesting that mechanotransduction by direct cell‐to‐cell connectivity is an essential feature in the NC phenotype.…”
mentioning
confidence: 99%
“…Similar to these cell lines, IVD cells with stably expressed Cas9 could aid in explaining the relationship between IVD genotype and phenotype in the future. Recent studies on IVD biology highlighted the importance of membrane proteins, namely, of cell surface receptors (eg, toll‐like receptor (TLR) TLR2), channels (eg, aquaporins, transient receptor potential cation channel subfamily V member 4 (TRPV4)), and adhesion molecules (eg, integrins) as these proteins allow IVD cells to sense their environment and respond to its changes. Although the expression and activity of these molecules are altered during DDD, understanding their exact function has been challenging so far as inhibitors/antagonists and activators/agonists are often nonselective or have short half‐lives .…”
Section: Targeted Genome Editing By Crispr/cas9mentioning
confidence: 99%
“…CRISPR/Cas9 also contributes to the study of genomic regions capable of molecular interactions thanks to the development of CRISPR engineered DNA‐binding molecule‐mediated chromatin immunoprecipitation (enChIP), where a specific antibody is fused to a dCas9 coexpressed with a gRNA . In IVD research, specifically in studies focusing on IVD oxygenation, enCHiP could, for example, be used to investigate the interaction between hypoxia‐responsive elements (HREs) and hypoxia‐inducible factors such as HIF‐1α . Another use of the CRISPR technology is the visualization of genomic loci in cell nuclei, or so‐called Cas9‐mediated fluorescence in situ hybridization (CASFISH) (Figure ).…”
Section: Targeted Genome Editing By Crispr/cas9mentioning
confidence: 99%